Comparative study of the factors that influence Behavioral Intentions in DANA and OVO users - Fahri, Fahri; Afifah, Nur; Juniwati, Juniwati; Purmono, Bintoro Bagus; Ahmadi, Ahmadi (Journal of Management and Digital Business, 2025)
This study compares DANA and OVO users in West Kalimantan to investigate the factors affecting e-wallet adoption. To ascertain the impact of compatibility, ubiquity, and social influence on behavioral intention with trust and satisfaction as intervening variables. Data was gathered from 300 respondents using a quantitative comparison approach and analyzed using PLS-SEM. The findings demonstrated that compatibility significantly affects trust and satisfaction, particularly for DANA users, raising their behavioral intention. On the other hand, there was no discernible variation in the impact of ubiquity on satisfaction. Furthermore, social influence had a different effect on trust in the two user groups, with DANA users being more affected. These findings emphasize compatibility and trust in promoting e-wallets, although ubiquity and social influence still need more study.